A kind of wave absorbing material and preparation method thereof

By introducing acrylic alkyl resin and phenolic resin into the absorbing material, forming a core-shell structure, and combining magnetic field orientation treatment and coupling agent, the problem of insufficient performance of existing electromagnetic absorbing patches in high temperature environments is solved, and the High high temperature resistance and high magnetic permeability of wave absorbing materials.

CN118580731BActive Publication Date: 2025-01-10ZHEJIANG YUANBANG MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411075361.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-01-10
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

The existing electromagnetic wave absorbing patches are prone to softening, thickening, powdering, cracking, cracking or foaming in high-temperature environments, resulting in insufficient high-temperature resistance in the surface assembly of electronic components such as chip components, increasing production costs and Waste of resources.

Method used

Using an absorbing material with a core-shell structure, the high-temperature and high-pressure coating layer is formed by adding alkyl acrylic resin and phenolic resin to the absorbing material, and combining magnetic field orientation treatment and coupling agent to improve the high-temperature resistance of the material and Permeability.

Benefits of technology

It significantly improves the high temperature resistance and magnetic permeability of wave absorbing materials, ensures that there is no morphological phenomenon in high temperature environments, reduces production costs, and improves the density and service life of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580731B_ABST
    Figure CN118580731B_ABST
Patent Text Reader

Abstract

The present invention provides an absorbing material and a preparation method thereof. The absorbing material has a core-shell structure, and the absorbing material includes a core layer and a coating layer, and the core layer includes soft magnetic powder; in the absorbing material, the content of the soft magnetic powder is 70-90% by mass percentage; wherein the raw materials for preparing the coating layer include acrylic alkyl resin and phenolic resin, and the acrylic alkyl resin: phenolic resin is calculated by mass ratio = 1-10:1, and the molding of the coating layer includes high temperature and high pressure treatment of the raw materials, and the temperature condition of the high temperature hot pressing treatment is 135-185°C and the pressure condition is 5-15MPa. The scheme provided by the present invention can make the acrylic alkyl resin and the phenolic resin tightly and evenly wrapped on the surface of the soft magnetic powder, forming a unique core-shell structure, and realizing high-density filling of the soft magnetic powder, so that the absorbing material provided by the present application not only has good high temperature resistance, but also has high magnetic permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wave absorbing materials, and in particular relates to a wave absorbing material and a preparation method thereof. Background Art

[0002] With the rapid development of electronic technology, especially power electronics technology, it has gradually become a fact that its systems, equipment and various components are developing towards high frequency, digitalization, integration, light and small size, high power density and low voltage of electronic circuits. For this reason, such modern electronic equipment will inevitably be adversely affected by more serious and complex stray magnetic fields than previous equipment, which is often called electromagnetic interference (EMI). Therefore, in the existing technology, the problem of electromagnetic compatibility (EMC) generally appears in the design of products (including systems and components). Usually, electromagnetic absorbing patches are used as a solution to suppress noise electromagnetic waves of various electronic instruments.

[0003] For the surface assembly technology of electronic components such as chip components on substrates, reflow soldering has become a basic process. The electromagnetic absorbing patches provided in the prior art lack heat resistance. When they pass through the reflow furnace, they are heated and inevitably soften and become thicker. The emergence of these problems easily leads to localized powdering, cracking, fissures, foaming and other poor morphological phenomena of the electromagnetic absorbing patches. Therefore, the electromagnetic absorbing patches provided in the prior art cannot be used in a high-temperature atmosphere such as reflow soldering. As a result, the surface assembly of electronic components such as chip components on substrates must first be reflow soldered before the electromagnetic absorbing patches are attached to the product surface, which greatly increases the waste of labor resources in production. Summary of the invention

[0004] In order to improve the high temperature resistance of the absorbing material and increase the magnetic permeability of the absorbing material, the present application provides an absorbing material and a preparation method thereof.

[0005] According to one aspect of the present invention, a wave absorbing material is provided, which has a core-shell structure, and the wave absorbing material includes a core layer and a coating layer, and the core layer includes soft magnetic powder; in the wave absorbing material, the content of soft magnetic powder is 70-90% by mass percentage; wherein, the raw materials for preparing the coating layer include acrylic alkyl resin and phenolic resin, and the acrylic alkyl resin: phenolic resin is calculated by mass ratio = 1-10:1, and the molding of the coating layer includes high temperature and high pressure treatment of the raw materials, and the temperature condition of the high temperature hot pressing treatment is 135-185°C and the pressure condition is 5-15MPa. The present invention can significantly enhance the high temperature resistance of the wave absorbing material by introducing acrylic alkyl resin and phenolic resin. Moreover, under the appropriate ratio of acrylic alkyl resin to phenolic resin, the wave absorbing material provided by the present invention can make the acrylic alkyl resin and phenolic resin tightly and evenly wrapped on the surface of the soft magnetic powder, thereby forming a unique core-shell structure. Therefore, the wave absorbing material provided by the present application can realize high-density filling of soft magnetic powder, so that the wave absorbing material provided by the present application not only has good high temperature resistance, but also has high magnetic permeability.

[0006] Preferably, the D of the soft magnetic powder is 50 The particle size of the soft magnetic powder is 45-65 μm; and / or the bulk density (AD) of the soft magnetic powder is 0.38-0.45 g / cm 3 ; and / or, the specific surface area (SSA) of the soft magnetic powder is 45~50m 2 / g. Furthermore, by adjusting the particle size, bulk density and specific surface area of ​​the soft magnetic powder used in the present application, the surface formed by the soft magnetic powder in the application can be made flatter and smoother. The higher the flattening degree of the soft magnetic powder, the higher the magnetic permeability of the obtained absorbing material under the condition of the same soft magnetic powder content.

[0007] Preferably, the soft magnetic powder includes at least one of iron-silicon-aluminum soft magnetic powder (Fe-Si-Al), iron-nickel soft magnetic powder (Fe-Ni), chromium-iron soft magnetic powder (Fe-Cr), and iron-silicon-chromium soft magnetic powder (Fe-Si-Cr).

[0008] Preferably, the glass transition temperature of the acrylic alkyl resin is -50~110°C. In actual industrial production, it is necessary to consider the problems of uneven dispersion, frictional heat affecting normal reaction, and difficulty in dissolving at room temperature that occur during the preparation process. The present application controls the range of the acrylic alkyl resin used by the glass transition temperature, thereby achieving uniform dispersion of the reaction system at room temperature and reducing reaction energy consumption, thereby reducing production costs.

[0009] Preferably, the acrylic alkyl resin includes at least one of methacrylate, methyl methacrylate, ethyl methacrylate, ethyl acrylate, butyl acrylate, and pentyl acrylate.

[0010] Preferably, the glass transition temperature of the phenolic resin is 20-200°C.

[0011] Preferably, the molecular weight of the phenolic resin is 2,000-200,000.

[0012] Preferably, the melting point of the phenolic resin is 120-300°C.

[0013] Preferably, the phenolic resin is prepared by a condensation reaction of a phenolic compound and an aldehyde compound, wherein the phenolic compound includes at least one of 2-tert-butylphenol, bisphenol A, and cresol, and / or the aldehyde compound includes at least one of formaldehyde, acetaldehyde, octanal, nonanal, decanal, undecanal, lauryl aldehyde, benzaldehyde, phenylacetaldehyde, phenylpropionaldehyde, citral, citronellal, hydroxycitronellal, perillaldehyde, and trimethylheptenal.

[0014] Preferably, the absorbing material further includes an interlayer, wherein the absorbing material is arranged from the center to the outside in sequence including a core layer, an interlayer, and a coating layer; the raw material for preparing the interlayer includes a coupling agent, and the amount of the coupling agent added is 2-10% of the mass of the soft magnetic powder. The introduced coupling agent can react with the resin and the soft magnetic powder, and can further improve the surface compatibility between the soft magnetic powder and the resin, making the core-shell structure of the absorbing material more stable, and helping to further increase the content of the soft magnetic powder, thereby improving the magnetic permeability of the absorbing material.

[0015] Preferably, the coupling agent includes a silane coupling agent. The silane coupling agent can react with the hydroxyl groups on the surface of the soft magnetic powder to form a silicon-oxygen bond, which can further enhance the chemical bonding between the acrylic alkyl resin, the phenolic resin and the soft magnetic powder, thereby enhancing the interfacial bonding force of the composite material. By adding the silane coupling agent, the compatibility, wettability and bonding force of the resin to the soft magnetic powder can be increased, and the silane coupling agent helps to improve the slurry viscosity during the preparation process, which is beneficial to the effective wetting and uniform bonding of the resin to the soft magnetic powder.

[0016] Preferably, the thickness of the core layer is not higher than 1000 nm; the thickness of the interlayer is not higher than 100 nm; and / or the thickness of the cladding layer is not higher than 200 nm.

[0017] Preferably, the thickness of the absorbing material is 50-500 μm.

[0018] Preferably, the raw materials for preparing the absorbing material further include an auxiliary agent, and the auxiliary agent includes at least one of a wetting agent and a defoaming agent.

[0019] Preferably, in the raw materials for preparing the absorbing material, the content of the auxiliary agent is 0.1-0.9% of the mass of the soft magnetic powder.

[0020] Another aspect of the present invention provides a method for preparing the above-mentioned absorbing material, which comprises the following steps: S1. After mixing the raw materials for preparing the absorbing material, the viscosity of the reaction mixture is controlled to be 20000-50000mpa / s by adding a solvent, and then reacting at room temperature for 2-4 hours to obtain a slurry; S2. Then the slurry is coated on the surface of the film, and a dry film is obtained after magnetic field orientation treatment and drying treatment in sequence; S3. The dry film is subjected to high-temperature hot pressing treatment to obtain the absorbing material, wherein the reaction temperature of the high-temperature hot pressing treatment is 135-185°C and the reaction pressure is 5-15MPa. The method provided by the present invention achieves directional arrangement of soft magnetic powder by using magnetic field orientation treatment, which is conducive to improving the density of the product, thereby improving the magnetic permeability of the product. In addition, the present invention can improve the molding problem of the absorbing material, as well as the performance of the formed product (such as magnetic permeability) and the appearance of the product (such as whether the product is powdering, bubbling, or rough) by regulating the reaction temperature and reaction pressure in the high-temperature hot pressing treatment.

[0021] Preferably, the solvent includes at least one of a ketone solvent, a vinegar solvent, an aromatic solvent, a cellosolve solvent, an ether solvent, and an aprotic polar solvent.

[0022] Preferably, the ketone solvent includes at least one of methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone and isophorone.

[0023] Preferably, the vinegar solvent includes at least one of ethyl acetate and butyl acetate.

[0024] Preferably, the aromatic solvent includes at least one of toluene and xylene.

[0025] Preferably, the cellosolve solvent includes at least one of cellosolve acetate and methyl cellosolve.

[0026] Preferably, the ether solvent includes at least one of tetrahydrofuran and diglyme.

[0027] Preferably, the aprotic polar solvent includes at least one of isopropanol, n-butanol and dimethylformamide.

[0028] Preferably, the stirring rate of the reaction in S1 is 1500-2500 r / min.

[0029] Preferably, the thickness of the dry film is 60-200 μm.

[0030] Preferably, in S3, at least one layer of dry film may be stacked and the absorbing material may be prepared by high-temperature hot pressing. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the absorbing material provided for this application;

[0032] Description of the accompanying drawings: 1. cladding layer; 2. interlayer; 3. core layer;

[0033] Figure 2 This is a test graph of the magnetic permeability of the absorbing material obtained by processing group 1A of Example 1;

[0034] Figure 3 This is a SEM image of the absorbing material prepared in treatment group 1C of Example 3. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0036] Example 1

[0037] Treatment Group 1A

[0038] 1. Raw materials for preparing absorbing materials

[0039] The raw materials for preparing the absorbing material in this embodiment are shown in Table 1. Among them, according to the mass fraction, this embodiment also introduces 0.8 parts of wetting agent and 0.8 parts of defoaming agent; the specific size of the soft magnetic powder introduced is: D 50 =60.4μm, AD=0.41g / cm 3 ,SSA=49m 2 / g; Phenolic resin is made by condensation of 2-tert-butylphenol and formaldehyde.

[0040] Table 1. Raw materials for preparing absorbing materials

[0041]

[0042] 2. Method for preparing microwave absorbing material

[0043] S1. After mixing the raw materials for preparing the absorbing material, the viscosity of the reaction mixture was controlled to 30000 mpa / s by adding a solvent, and then reacted at room temperature at a stirring rate of 2000 r / min for 4 hours to obtain a slurry;

[0044] S2. The slurry is then coated on the surface of the PET film, and then subjected to magnetic field orientation treatment and drying treatment to obtain a dry film with a thickness of 0.1 mm;

[0045] S3. The dry film is subjected to high temperature hot pressing to obtain an absorbing material.

[0046] The treatment groups 2A to 6A and the comparative groups 1A to 2A of Example 1 prepared the absorbing materials with reference to the formula and method provided by the treatment group 1A of Example 1, respectively using the materials of the acrylic alkyl resin, the materials of the phenolic resin, and the mass ratio of the acrylic alkyl resin to the phenolic resin (acrylic alkyl resin: phenolic resin) used in the formula as variables, and the variables used to prepare the absorbing materials of the treatment groups 1A to 6A and the comparative groups 1A to 2A of Example 1 are shown in Table 2. Except for the above differences, the operation steps for preparing the absorbing materials of the treatment groups 2A to 6A and the comparative groups 1A to 2A of Example 1 are strictly consistent with those of the treatment group 1A of Example 1.

[0047] Among them, in treatment groups 1A~3A and comparison groups 1A~2A, the total mass fractions of acrylic acid alkyl resin and phenolic resin were kept unchanged, and only the mass ratio of the two was changed; in treatment groups 4A~6A, the materials of acrylic acid alkyl resin and the materials used to prepare phenolic resin were used as variables. The phenolic resin provided in Table 2 refers to the phenolic resin prepared by a condensation reaction of the corresponding phenolic compound and the aldehyde compound.

[0048] Table 2. Variables involved in treatment groups 1A-6A and comparison groups 1A-2A in Example 1

[0049]

[0050] Comparative group 3A

[0051] The comparative group prepared the absorbing material by referring to the formula and method provided by the treatment group 1A of Example 1. The difference from the treatment group 1A of Example 1 is that the methyl methacrylate was replaced by polyether polyurethane (polytetrahydrofuran alcohol) in equal parts by weight when preparing the absorbing material. Except for the above differences, the operation steps for preparing the absorbing material in the comparative group were strictly consistent with those of the treatment group 1A of Example 1.

[0052] Comparative group 4A

[0053] This comparative group prepared the absorbing material by referring to the formula and method provided by the treatment group 1A of Example 1. The difference from the treatment group 1A of Example 1 is that when preparing the absorbing material, the comparative group used 2,3-epoxypropyl methacrylate (glycidyl methacrylate) in equal parts by mass to replace methyl methacrylate. Except for the above differences, the operation steps for preparing the absorbing material in this comparative group are strictly consistent with those of the treatment group 1A of Example 1.

[0054] Comparative group 5A

[0055] This comparative group prepared the absorbing material by referring to the formula and method provided by the treatment group 1A of Example 1. The difference from the treatment group 1A of Example 1 is that the methyl methacrylate was replaced by phenyl acrylate in equal parts by weight when preparing the absorbing material. Except for the above differences, the operation steps for preparing the absorbing material in this comparative group are strictly consistent with those of the treatment group 1A of Example 1.

[0056] Test Example 1

[0057] 1. Test subjects

[0058] The microwave absorbing materials prepared in the treatment groups 1A-6A and the comparison groups 1A-5A provided in Example 1.

[0059] 2. Test Method

[0060] This test example was carried out according to the following method, wherein the temperature and humidity of the test room were controlled as follows: temperature 23°C ± 3°C; humidity: 50RH ± 10%.

[0061] (1) Magnetic permeability: The material was cut into rings with an inner diameter of 9 mm and an outer diameter of 16 mm on a mold and tested on an E4991B precision impedance analyzer.

[0062] (2) Stiffness: Cut the sample into pieces of 7 cm*3.8 cm and test it on a bending stiffness tester.

[0063] (3) Density: tested using the Archimedes drainage method.

[0064] (4) Thickness: measured with a micrometer or micrometer screw.

[0065] (5) Reflow test: It is necessary to observe the thickness change and surface morphology change of the product; in terms of surface thickness, the electromagnetic absorbing material is cut into 5cm×5cm patches, 9 different points are randomly selected and marked on the patch, and the thickness of the patch at the 9 points is measured using a spiral micrometer. Then the patch material is placed in a reflow machine at 260℃ and heated according to the reflow curve. After taking it out, the thickness of the 9 points is measured again, and the thickness change rate at each point after high temperature treatment is calculated respectively, and the average value of the thickness change rate of the 9 points is calculated. In terms of surface morphology, after taking out the product, check whether the surface has any morphological defects such as powdering, cracking, cracks, and foaming.

[0066] (6) Tin furnace test: A microcomputer lead-free pure titanium tin melting furnace is used for testing. The specific method is: set the temperature of the test equipment to 280°C, wait until the temperature rises to 280°C, put in the solder wire, dissolve it, lay the test sample flat on the solution, leave it for 30 seconds, and then take it out to observe whether the surface has powdering, cracking, cracks, foaming and other poor morphological phenomena, and measure whether the product thickness has changed.

[0067] 3. Test results and analysis

[0068] The data of this test example are shown in Table 3. In the treatment groups 1A to 3A and the comparison groups 1A to 2A of Example 1, it can be seen from the test that as the content of acrylic acid alkyl resin increases, the high temperature resistance of the obtained absorbing material shows a trend of first increasing and then decreasing. In addition, it can be found from the test that the mass ratio of acrylic acid alkyl resin to phenolic resin will affect the core-shell structure formed with the soft magnetic powder, such as Figure 1 As shown in the figure (coating layer 1 formed by acrylic alkyl resin and phenolic resin; interlayer 2 formed by silane coupling agent; core layer 3 formed by soft magnetic powder), which in turn affects the magnetic permeability of the absorbing material. The magnetic permeability test diagram of the absorbing material prepared by treatment group 1A of Example 1 is as follows: Figure 2 As shown (μ' represents the real part of relative magnetic permeability; μ" represents the imaginary part of relative magnetic permeability; μ' characterizes the degree of response of the material to magnetic flux under the action of magnetic field, and represents the magnetization intensity of the material in the magnetic field; μ" characterizes the material's ability to absorb or radiate magnetic field, and represents the loss characteristics of the material).

[0069] It can be seen from the treatment group 1A, treatment groups 4A~5A and comparison groups 3A~5A of Example 1 that different acrylic resins will affect the performance of the prepared absorbing material. Among them, when the acrylic resin is an acrylic alkyl resin with a saturated alkyl chain structure, the prepared absorbing material has better high temperature resistance than the epoxy acrylic resin or aromatic acrylic resin with an unsaturated structure. In addition, in treatment group 5A, since the glass transition temperature of the acrylic alkyl resin used is -69°C, which does not meet the requirements of -50~110°C, it causes problems such as uneven dispersion during the preparation process, which reduces the high temperature resistance of the prepared absorbing material.

[0070] Table 3. Test results of test case 1

[0071]

[0072] Example 2

[0073] The treatment group 1B of Example 2 was prepared in strict accordance with the formula and method provided by the treatment group 1A of Example 1 to prepare the absorbing material. The treatment groups 2B~6B of Example 2 and the comparative groups 1B~2B were prepared with reference to the formula and method provided by the treatment group 1B of Example 2 to prepare the absorbing material, with the content, type and size of the soft magnetic powder used in the formula as variables. The variables used for preparing the absorbing material by the treatment groups 1B~6B of Example 2 and the comparative groups 1B~2B are shown in Table 4. Except for the above differences, the operation steps for preparing the absorbing material by the treatment groups 2B~6B and the comparative groups 1B~2B of Example 1 were strictly consistent with those by the treatment group 1B of Example 2.

[0074] Table 4. Variables involved in treatment groups 1B-6B and comparison groups 1B-2B of Example 2

[0075]

[0076] Test Example 2

[0077] 1. Test subjects

[0078] The absorbing materials prepared in the treatment groups 1B-6B and the comparison groups 1B-2B provided in Example 2.

[0079] 2. Test Method

[0080] Refer to the method provided in Test Example 1.

[0081] 3. Test results and analysis

[0082] The data of this test example are shown in Table 5. It can be seen from the data provided by the treatment groups 1B~6B of Example 2 that the content, type and size of the soft magnetic powder will have a great influence on the magnetic permeability of the obtained absorbing material, and will further affect the density and stiffness of the formed absorbing material, thereby affecting the service life of the absorbing material. Among them, it can be seen from the above treatment groups that the type of magnetic powder has a greater impact on the magnetic permeability than the particle size of the magnetic powder (this is determined by the properties of the soft magnetic powder itself). In the comparison groups 1B~2B of Example 2, it can be seen that when there is too much soft magnetic powder in the absorbing material, the acrylic alkyl resin, phenolic resin and magnetic powder cannot form a uniform core-shell structure, and the soft magnetic powder will be exposed, resulting in the absorbing material being difficult to form during the high-temperature hot pressing stage, powder falling, and rough appearance. Serious adverse phenomena; when there is too little soft magnetic powder in the absorbing material, the magnetic permeability of the absorbing material will be significantly reduced, and the product will receive electromagnetic interference when using the absorbing material.

[0083] Table 5. Test results of test case 2

[0084]

[0085] Example 3

[0086] The treatment group 1C of Example 3 was strictly prepared according to the formula and method provided by the treatment group 1A of Example 1. The treatment groups 2C to 5C of Example 3 were prepared with reference to the formula and method provided by the treatment group 1C of Example 3, and the reaction temperature and reaction pressure involved in step S3 of the preparation method were used as variables. The variables used for preparing the absorbing materials by the treatment groups 1C to 5C of Example 3 are shown in Table 6. Except for the above differences, the operation steps for preparing the absorbing materials by the treatment groups 2C to 5C of Example 3 were strictly consistent with those of the treatment group 1C of Example 3.

[0087] Table 6. Variables involved in treatment groups 1C to 5C in Example 3

[0088]

[0089] Test Example 3

[0090] 1. Test subjects

[0091] The absorbing material prepared by processing groups 1C to 5C provided in Example 3.

[0092] 2. Test Method

[0093] Refer to the method provided in Test Example 1.

[0094] 3. Test results and analysis

[0095] The data of this test example are shown in Table 7. It can be seen from the data provided by the treatment groups 1C to 5C of Example 3 that the high temperature hot pressing treatment in step S3 of the preparation method will have a great impact on the magnetic permeability and product appearance of the obtained absorbing material. In addition, the preparation method provided by this scheme can achieve directional arrangement of the soft magnetic powder inside the absorbing material by using magnetic field orientation treatment. Among them, the soft magnetic powder in the absorbing material obtained by the treatment group 1C is arranged as follows: Figure 3 As shown in the figure (the thickness data in the figure is the thickness of the soft magnetic powder), that is, the soft magnetic powder is Figure 3 The orientation in the vertical direction shown is uniform, which is beneficial to improving the density of the product, thereby improving the magnetic permeability of the product.

[0096] Table 7. Test results of test case 3

[0097]

[0098] Example 4

[0099] The treatment group 1D of Example 4 was strictly prepared according to the formula and method provided by the treatment group 1A of Example 1. The treatment groups 2D to 6D of Example 4 were prepared with reference to the formula and method provided by the treatment group 1D of Example 4, with the type and amount of coupling agent added when preparing the absorbing material as variables. The variables used for preparing the absorbing material by the treatment groups 1D to 6D of Example 4 with reference to the treatment group 1D of Example 4 are shown in Table 8. Among them, the amount of coupling agent added is based on the mass of soft magnetic powder. In addition to the above differences, the operation steps for preparing the absorbing material by the treatment groups 2D to 6D of Example 4 are strictly consistent with those of the treatment group 1D of Example 4.

[0100] Table 8. Variables involved in treatment groups 1D to 6D in Example 4

[0101]

[0102] Test Example 4

[0103] 1. Test subjects

[0104] The absorbing material prepared by processing groups 1D~6D provided in Example 4.

[0105] 2. Test Method

[0106] Refer to the method provided in Test Example 1.

[0107] 3. Test results and analysis

[0108] The data of this test example are shown in Table 9. It can be seen from the data provided by treatment groups 1D to 5D of Example 4 that when preparing the absorbing material, as the content of the coupling agent increases, the magnetic permeability of the absorbing material prepared shows a trend of rising and then falling. This is because the coupling agent can react with the resin and the soft magnetic powder, and can further improve the surface compatibility between the soft magnetic powder and the resin, making the core-shell structure of the absorbing material more stable, which helps to further increase the content of the soft magnetic powder, thereby improving the magnetic permeability of the absorbing material. It can be seen from treatment groups 1D and 6D of the embodiment that the use of silane coupling agents will have a better enhancement effect. This is because the silane coupling agent can react with the hydroxyl groups on the surface of the soft magnetic powder to form a silicon-oxygen bond, which can further enhance the chemical bonding between the acrylic alkyl resin, the phenolic resin and the soft magnetic powder, thereby enhancing the interfacial bonding of the composite material. The addition of silane coupling agent can increase the compatibility, wettability and adhesion of the resin to the soft magnetic powder. In addition, the silane coupling agent helps to improve the viscosity of the slurry during the preparation process, which is beneficial to the effective wetting and uniform adhesion of the resin to the soft magnetic powder.

[0109] Table 9. Test results of test case 4

[0110]

[0111] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A wave absorbing material, characterized in that: The absorbing material has a core-shell structure, and the absorbing material includes a core layer, an interlayer, and a coating layer arranged from the center to the outside, and the core layer includes soft magnetic powder; in the absorbing material, the content of the soft magnetic powder is 70-90% by mass percentage; Wherein, the raw materials for preparing the interlayer include a coupling agent, and the amount of the coupling agent added is 2-10% of the mass of the soft magnetic powder; The raw materials for preparing the coating layer include alkyl acrylate and phenolic resin, and the mass ratio of the alkyl acrylate to the phenolic resin is 1-10:1; the alkyl acrylate is at least one of methyl methacrylate and butyl acrylate; The preparation of the absorbing material comprises the following steps: S1. After mixing the raw materials for preparing the absorbing material, the viscosity of the reaction mixture is controlled to 20000-50000 mpa / s by adding a solvent, and then reacting at room temperature for 2 to 4 hours to obtain a slurry; S2. The slurry is then applied to the surface of the film, and a dry film is obtained by sequentially subjecting the film to magnetic field orientation treatment and drying treatment; S3. The dry film is subjected to high temperature hot pressing treatment, wherein the temperature condition of the high temperature hot pressing treatment is 135-185° C. and the pressure condition is 5-15 MPa to obtain the absorbing material.

2. The absorbing material according to claim 1, characterized in that: The D 50 45~65μm; And / or, the bulk density of the soft magnetic powder is 0.38-0.45 g / cm 3 ; And / or, the specific surface area of ​​the soft magnetic powder is 45-50m 2 / g.

3. The absorbing material according to claim 1, characterized in that: The soft magnetic powder includes at least one of sendustine-aluminum soft magnetic powder, iron-nickel soft magnetic powder, chromium-iron soft magnetic powder and iron-silicon-chromium soft magnetic powder.

4. The absorbing material according to claim 1, characterized in that: The glass transition temperature of the alkyl acrylate is -50 to 110°C.

5. The absorbing material according to claim 1, characterized in that: The glass transition temperature of the phenolic resin is 20-200°C.

6. The absorbing material according to any one of claims 1 to 5, characterized in that: The phenolic resin is prepared by polycondensation of phenolic compounds and aldehyde compounds; Wherein, the phenolic compound includes at least one of 2-tert-butylphenol, bisphenol A and cresol; And / or, the aldehyde compound includes at least one of formaldehyde, acetaldehyde, octanal, nonanal, decanal, undecanal, lauryl aldehyde, benzaldehyde, phenylacetaldehyde, phenylpropionaldehyde, citral, citronellal, hydroxycitronellal, perillaldehyde, and trimethylheptenal.

7. The absorbing material according to claim 1, characterized in that: The coupling agent includes a silane coupling agent.

8. The absorbing material according to claim 1, characterized in that: The thickness of the core layer is not greater than 1000 nm; and / or, the thickness of the interlayer is not greater than 100 nm; And / or, the thickness of the coating layer is not higher than 200 nm.

Citation Information

Patent Citations

  • Soft magnetic alloy powder, wave absorption sheet, preparation method of soft magnetic alloy powder, electronic component and electronic equipment

    CN110060834A

  • Composite magnetic material

    US20150371743A1

  • Composite-type electromagnetic wave suppression body

    WO2016088826A1